Implementation Plan In Response To The Executive Board-Endorsed Recommendations From The IEO Evaluation Of The IMF's Financial Surveillance. (Policy Papers; Policy Paper ;, 2019)
The actions in this Management Implementation Plan aim at: -- Strengthening financial and macrofinancial analysis in Article IV consultations -- Refocusing FSAP country selection and scope -- Increasing traction of multilateral surveillance -- Enhancing the IMF's macrofinancial analysis toolkit -- Building financial skills and expertise at the Fund.